2006
DOI: 10.1128/aac.50.5.1696-1700.2006
|View full text |Cite
|
Sign up to set email alerts
|

Preclinical Safety and Efficacy Assessments of Dendrimer-Based (SPL7013) Microbicide Gel Formulations in a Nonhuman Primate Model

Abstract: Three gel formulations (1%, 3%, and 5% [wt/wt]) of SPL7013, a dendrimer known to have antiviral (anti-human immunodeficiency virus and anti-herpes simplex virus) activities, completed a range of preclinical tests in the pigtailed macaque models for vaginally and rectally applied topical microbicide safety assessments. The vaginal safety profile of the 3% SPL7013 gel formulation was equal to that of the 1% formulation but was superior to that of the 5% formulation. The 3% SPL7013 gel was further evaluated for r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
64
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(65 citation statements)
references
References 18 publications
0
64
0
1
Order By: Relevance
“…Vivagel®, developed by Starpharma (Melbourne, Australia), is a formulation of polyanionic lysine G4 dendrimers with an anionic surface of naphthalene-disulfonate (SPL7013) in a Carbopol® gel. It exhibits antiviral activity against HIV and HSV for the treatment of sexually transmitted infections and is given by intravaginal administration (152). Complete preclinical and phase I clinical studies have shown that 0.5-3% SPL7013 formulations are safe and well tolerated after seven-day vaginal application without systemic absorption (151)(152)(153).…”
Section: Perspective For Clinical Translationmentioning
confidence: 99%
See 1 more Smart Citation
“…Vivagel®, developed by Starpharma (Melbourne, Australia), is a formulation of polyanionic lysine G4 dendrimers with an anionic surface of naphthalene-disulfonate (SPL7013) in a Carbopol® gel. It exhibits antiviral activity against HIV and HSV for the treatment of sexually transmitted infections and is given by intravaginal administration (152). Complete preclinical and phase I clinical studies have shown that 0.5-3% SPL7013 formulations are safe and well tolerated after seven-day vaginal application without systemic absorption (151)(152)(153).…”
Section: Perspective For Clinical Translationmentioning
confidence: 99%
“…It exhibits antiviral activity against HIV and HSV for the treatment of sexually transmitted infections and is given by intravaginal administration (152). Complete preclinical and phase I clinical studies have shown that 0.5-3% SPL7013 formulations are safe and well tolerated after seven-day vaginal application without systemic absorption (151)(152)(153). A phase II clinical trial of Vivagel® is ongoing with fast track status.…”
Section: Perspective For Clinical Translationmentioning
confidence: 99%
“…SPL7013 has demonstrated low toxicity in cervical and colorectal epithelial cell lines, peripheral blood mononuclear cells (PBMCs), and macrophages and does not impair the resistance of polarized epithelial cells (6). VivaGel has demonstrated favorable safety profiles when administered vaginally and rectally in macaques (16) (4). It is effective in preventing the vaginal transmission of the CXCR4 SHIV89.6P strain in macaques and SHIV162P3 infection of macaque PBMCs (11).…”
mentioning
confidence: 99%
“…Several trials have been conducted to evaluate the safety and eicacy of this product. These studies unanimously describe that SPL7013 is nontoxic and safe to use even at very high concentrations of (1000 μg/ml) [112,114]. Likewise, in …”
Section: Vivagelmentioning
confidence: 99%